2013
DOI: 10.1161/circimaging.112.000176
|View full text |Cite
|
Sign up to set email alerts
|

Regions of Low Endothelial Shear Stress Colocalize With Positive Vascular Remodeling and Atherosclerotic Plaque Disruption

Abstract: 2; P<0.001) compared with nondisrupted plaques. The peak ESS negatively correlated with the plaque area (r=−0.56, P<0.001) and remodeling ratio (r=−0.4, P=0.008). There was also a negative correlation between the mean ESS and the remodeling ratio (r=−0.55, P<0.001). Both the peak ESS and the mean ESS did not correlate with the % stenosis; there was a weak but statistically significant correlation with the % cross-sectional narrowing (r=0.3, P=0.002 and r=0.2, P=0.04, respectively). Receiver operating character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 56 publications
6
22
0
Order By: Relevance
“…In that study, the authors indicate that the vulnerable plaques are associated with a biomechanical self-feeding cycle causing an excessive expansive remodelling (outward remodelling) whereas stenotic remodelling induces stable plaques. Similar conclusions related to the link between vulnerability and remodelling are presented by Phinikaridou et al [33] in a study conducted on white rabbit abdominal aortas. However, WSS amplitude does not seem to be the only criterion for plaque stability and mouse cuff models have been developed to study the oscillatory characteristics of the wall shear stress [35] .…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In that study, the authors indicate that the vulnerable plaques are associated with a biomechanical self-feeding cycle causing an excessive expansive remodelling (outward remodelling) whereas stenotic remodelling induces stable plaques. Similar conclusions related to the link between vulnerability and remodelling are presented by Phinikaridou et al [33] in a study conducted on white rabbit abdominal aortas. However, WSS amplitude does not seem to be the only criterion for plaque stability and mouse cuff models have been developed to study the oscillatory characteristics of the wall shear stress [35] .…”
Section: Introductionsupporting
confidence: 87%
“…As plaques develop, they may cause luminal narrowing, leading to a reduction in vessel volume, or undergo expansive remodelling to maintain lumen diameter [2, 24, 32, 33] . This remodelling has been first underlined by Glagov et al [34] for coronary arteries in which Chatzizisis et al [2] suggest that low WSS causes intense inflammation, excessive wall and lumen expansion inducing outward plaque formation, and that arterial sections with slightly low WSS induce limited inflammation and lipid accumulation, leading to stenotic shape remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is unknown to what extent high blood pressure contributes to the vulnerable phenotype in the upstream low-flow region compared to the downstream, oscillatory, low-pressure regions. In other models, both low shear and transverse shear were strongly correlated with regions of vulnerability within plaques (77)(78)(79). Plaque rupture itself also depends on wall strain.…”
Section: Plaque Progression and Remodelingmentioning
confidence: 79%
“…Low WSS regions are present within proximal vessels and on the contralateral wall to arterial side-branch divisions 12 . Animal studies using a partial arterial ligation model showed that co-localisation of low and oscillatory WSS acted synergistically to promote atherogenesis 75 , whereas low WSS was associated with plaque burden and positive remodelling 76 . Similarly, the spatial and temporal relationship between low WSS and plaque progression was illustrated through longitudinal animal studies.…”
Section: Plaque Growth and Arterial Remodellingmentioning
confidence: 99%